(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
SAIs has a pivotal role in enhancing public sector performance through its quest to achieve the greatest possible efficiency and effectiveness in its, so it has to adopt applied framework for abilities building, the research aims to shed light on the role of SAIs and the nature of their work, and the definition for its abilities building, and to prepare a proposal for abilities building applied to work with the SAI in the Republic of Iraq (of the Federal Board of Supreme Audit ),the Researchers reached conclusions, namely: abilities building is the outcome of the interaction between the reality of all of the employees of the SAI and the institution itself and the environment and the specific requirements of the development of this situation on an ongoing basis, the overall percentages to test the proposed abilities building guide in the Federal Board of Supreme Audit to achieve a modest level in the field of abilities building as ratios were as follows (60% applied entirely to,20% partially implemented, 20% of the Not Applicable), the researchers presented a set of recommendations including: give greater attention to building abilities and their development in SAIs in way that reflected a positive impact on the performance of the device, and FBSA initiates in earnest and practical in building its abilities.